Occurrence and risk assessment of endocrine-disrupting chemicals in wastewater treatment plants in the Chaohu Lake Basin - Han, Yalin; Qi, Cuicui; Niu, Ziniu; Li, Nini; Tang, Jie (Frontiers in Environmental Science, 2024)
Introduction: Endocrine-disrupting chemicals (EDCs) in effluent and residual sludge from wastewater treatment plants (WWTPs) pose significant environmental and human health risks due to their persistence, bioaccumulation, and difficulty in detection and degradation. This study investigates the environmental exposure and risks associated with EDCs in effluent and sludge from four WWTPs: Tangxi River (TXH), Zipeng Mountain (ZPS), Lianxi (LX), and Wang Xiaoying (WXY). Methods: Environmental exposure indexes of EDCs were assessed in the effluent and sludge of the four WWTPs across four seasons (spring, summer, autumn, and winter) from October 2017 to October 2018. Detection rates of various pollutants, their seasonal and spatial characteristics, and removal rates were analyzed. Positive matrix factorization (PMF) was used for source analysis under influent data, and an ecological risk assessment was conducted using the risk quotient (RQ) method. Results: The study found 4-n-nonylphenol (NP) and di-2-ethylhexyl phthalate (DEHP) had 100% detection rates in the effluent of all four WWTPs, while only DEHP showed a 100% detection rate in the sludge. Bisphenol A (BPA) exhibited the highest concentration in the TXH effluent during autumn. Benzo(a)pyrene (B(a)P) was detected only in the sludge during spring and summer and in the effluent of TXH and WXY. PMF source analysis indicated industrial wastewater discharge as the primary source of pollutants. Ecological risk assessment revealed a high RQ for estriol (E3) in TXH effluent during autumn, and DEHP presented a potential carcinogenic risk through drinking water. Discussion: The findings highlight significant seasonal and spatial variations in EDC concentrations and removal rates across the WWTPs. The persistent presence of DEHP and the high-risk levels of E3 in specific seasons underscore the need for improved treatment processes and stricter industrial discharge regulations to mitigate EDC-related risks. Further research is recommended to explore advanced detection and degradation techniques for EDCs in WWTPs.